The Need for Innovative Technologies and Domestic Journalism - Asanov Л.Д.; Daulen М.Б. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2022)
The article provides an overview of the need for innovation technology development and potentials of domestic journalism. It also covers the history of Kazakhstan’s first media holdings and based on specific examples it demonstrated the first results of Kazakhstani media in the global information technology potential. The article on convergent journalism and its effectiveness is written in relevant time. The article discusses the impact of new information technologies on media communication, the radical impact of modern media transformations. It focuses on the history of information communication. The main task is the economic direction of the media and the activities of the journalist, which are carried out via market mechanisms during the dominant period of commercial journalism.